Time Management Scale among Indonesian Students: Validity and Reliability Analysis - Riza Noviana Khoirunnisa; Chinun Boonroungrut; Damajanti Kusuma Dewi (Universitas Ahmad Dahlan, 2026)
Time management is an essential self-regulatory skill that supports students’ learning quality and academic performance. However, measurement tools require cultural and linguistic validation before being applied in new contexts. This study adapted the Time Management Scale (TMS) for Indonesian university students and evaluated its construct validity and reliability. A quantitative cross-sectional design was used with 404 respondents selected through purposive sampling. Confirmatory factor analysis (CFA) was applied to test factorial validity, and psychometric quality was assessed using composite reliability and average variance extracted (AVE) as indicators of construct reliability and convergent validity. The results provided evidence of an acceptable model fit and satisfactory psychometric performance for the refined measurement model. Through iterative item evaluation, the scale was reduced to a parsimonious 12-item version while maintaining its theoretical structure. In conclusion, the Indonesian-adapted TMS offers initial evidence of validity and reliability for assessing students’ time management in Indonesian higher education settings.